Is there any more context to your question?
Answer:
x = - 3
Step-by-step explanation:
g(x) = 4x + 1...... (1)
g(x) = -11.... (2)
From equations (1) & (2)
-11 = 4x + 1
-11 - 1 = 4x
-12 = 4x
-12/4 = x
-3 = x
x = - 3
Answer:
-7
Step-by-step explanation:
-3-(-10)/-2+1
-3-5+1
-8+1
-7
To solve for r, you would start by subtracting p from both sides.
2m - p = -q/r
Multiply everything by r.
2mr - pr = -q
Factor r out of the left side of the equation.
r(2m - p) = -q
Divide both sides by (2m - p).
r =
.
The milk is the dependent variable